Where the money comes from : a brief account of the role of investment banking in American history and its place in the economy today - Clark, Fred G.; Rimanoczy, Richard Stanton (Princeton, N.J.: Van Nostrand, 1961)
The book highlighted the limited knowledge of many business men concerning the historic performance of investment banking in the development of the United States and the present position of that profession in relation to the current financial problems of business.
usc 21/09/2017
Loans
Keywords: Investment banking; United States